ANALYSIS OF JUDGES' DECISIONS REGARDING DIVORCE CASES WITH DIGITAL EVIDENCE IN THE SAMARINDA RELIGIOUS COURT - Delvina Tri Agustin; Bambang Iswanto; Nur Syamsi (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
The legal force of digital evidence submitted by litigants in divorce hearings in religious courts is the background for this research. The method used in this study is normative legal research with a normative analytical juridical approach to judges' decisions in divorce cases as the object of research. So that researchers can answer problems by conducting literature research from relevant legal sources.The judge's consideration in deciding the case is in the law relating to Marriage, the stages of the trial procedure, the legal basis of the case, the legal basis for evidence, the legal basis for the reason or cause of divorce, and the legal basis for the authority of the judge. Meanwhile, the position of digital evidence itself as one of the evidence of confessions that is stamped and used by the judge as the main case for the cause of divorce.The judge did not use Law No. 11 of 2008 on electronic information on digital evidence but focused on Jurisprudence which gave birth to rules on the examination of divorce on the grounds of Article 19 letter (f) of Government Regulation No. 9 of 1975 jo Article 116 of the Compilation of Islamic Law, where the doctrine that must be applied in divorce cases is not